Analysis of genome-wide 5-hydroxymethylation of blood samples stored in different anticoagulants: opportunities for the expansion of clinical resources for epigenetic research - Lu Gao; Zhou Zhang; Xiao-Long Cui; Diana West-Szymanski; Chang Ye; Chuan He; Wei Zhang; Marc Bissonnette (Epigenetics, 2023)
ABSTRACTBackground: Elucidating epigenetic mechanisms could provide new biomarkers for disease diagnosis and prognosis. Technological advances allow genome-wide profiling of 5-hydroxymethylcytosines (5hmC) in liquid biopsies. 5hmC-Seal followed by NGS is a highly sensitive technique for 5hmC biomarker discovery in cfDNA. Currently, 5hmC Seal is optimized for EDTA blood collection. We asked whether heparin was compatible with 5hmC Seal as many clinical and biobanked samples are stored in heparin.Methods: We obtained 60 samples in EDTA matched to 60 samples in heparin from the Prostate, Lung, Colorectal, and Ovarian (PLCO) Cancer Screening Trial. Samples were comprised of 30 controls and 30 individuals who were later diagnosed with colon cancer. We profiled genome-wide 5hmC in cfDNA using 5hmC-Seal assay followed by NGS. The 5hmC profiling data from samples collected in EDTA were systematically compared to those in heparin across various genomic features.Results: cfDNA isolation and library construction appeared comparable in heparin vs. EDTA. Typical genomic distribution patterns of 5hmC, including gene bodies and enhancer markers, were comparable in heparin vs. EDTA. 5hmC analysis of cases and controls yielded highly correlated differential features suggesting that both anticoagulants were compatible with 5hmC Seal assay.Conclusions: While not currently recommended for the 5hmC-Seal protocol, blood samples stored in heparin were successfully used to generate analysable and biologically relevant genome-wide 5hmC profiling. Our findings are the first to support opportunities to expand the biospecimen resource to heparin samples for 5hmC Seal and perhaps other PCR-based technologies in epigenetic research.